Analisa Audit Internal Terhadap Kinerja Keuangan Berdasarkan Literatur Review Terindeks Sinta - Rina Mulyani; Oktianasekar; Denadya Putri Wijaya3; Annisa Putri; Tio Pratiwi; Rachmat Agus Santoso (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to discover the consistency in previous research indicating the positive influence of internal audit on company financial performance. Qualitative methodology with a literature review approach is employed to strengthen arguments with information collected from articles published in national journals. The research identifies several factors influencing the relationship between internal audit and financial performance, including management roles, financial reporting quality, and external environmental factors that can moderate this relationship, providing a more comprehensive understanding of the impact of internal audit on company financial performance.